Diacylglycerols interact with the L2 lipidation site in TRPC3 to induce a sensitized channel state. (23rd May 2022) - Erkan‐Candag, Hazel; Clarke, Amy; Tiapko, Oleksandra; Gsell, Mathias AF; Stockner, Thomas; Groschner, Klaus
Abstract: Coordination of lipids within transient receptor potential canonical channels (TRPCs) is essential for their Ca 2+ signaling function. Single particle cryo‐EM studies identified two lipid interaction sites, designated L1 and L2, which are proposed to accommodate diacylglycerols (DAGs). To explore the role of L1 and L2 in TRPC3 function, we combined structure‐guided mutagenesis and electrophysiological recording with molecular dynamics (MD) simulations. MD simulations indicate rapid DAG accumulation within both L1 and L2 upon its availability within the plasma membrane. Electrophysiological experiments using a photoswitchable DAG‐probe reveal potentiation of TRPC3 currents during repetitive activation by DAG. Importantly, initial DAG exposure generates a subsequently sensitized channel state that is associated with significantly faster activation kinetics. TRPC3 sensitization is specifically promoted by mutations within L2, with G652A exhibiting sensitization at very low levels of active DAG. We demonstrate the ability of TRPC3 to adopt a closed state conformation that features partial lipidation of L2 sites by DAG and enables fast activation of the channel by the phospholipase C‐DAG pathway. Synopsis: Diacylglycerols (DAGs) sensitize TRPC channels by interactions with the L2 lipidation site in the channel´s pore domain. The DAG sensitized state enables fast channel activation and a high‐activity Ca 2+ signaling mode. DAGs control TRPC functions by binding to the L2 lipidation site. At low levels, DAGs induce a sensitized state without increasing open probability. Sensitizing DAG‐L2 interactions tune channel functions towards fast activation and high‐gain Ca 2+ signaling function. Abstract : Diacylglycerols (DAGs) sensitize TRPC channels by interactions with the L2 lipidation site in the channel´s pore domain. The DAG sensitized state enables fast channel activation and a high‐activity Ca 2+ signaling mode.